PENERAPAN SISTEM AKUNTANSI PADA PERUSAHAAN DAGANG “MUHISSHOP_SYARIFAH” - Agnia nurul ilmi; Eneng irmayanti; Luvita hesti jandriani; Shely safitri; Vani aulia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This report discusses company financial management and recording financial transactions. The primary focus covers general accounting systems, including credit sales, purchases, inventory, payroll, and cash receipts. It explains how the accounting system works, from recording transactions to making financial reports, helping to understand how to make company financial records. Credit sales and purchase systems are outlined, making it easier for companies to record and manage transactions where customers pay later. Purchasing system discussions help companies manage bills and make efficient purchasing decisions. Inventory is considered to maintain order and count goods accurately. Accounting systems also help companies pay salaries, including calculating taxes and other deductions. Recording the receipt of money, whether via cash, check, or electronic transfer, helps a company track its liquidity. With an understanding of how these systems operate, this report provides a clear and concise picture of a company's financial management and smart financial decision making